Innovation and practice of secondary development technology for China’s first long-term abandoned deepwater oilfield - WEN Xing,WANG Kun,XIE Mingying,FENG Shasha,LI Li,LI Wei (Youqicang pingjia yu kaifa)
China’s first long-term abandoned deepwater oil field has become a marginal oil field that is difficult to exploit due to complex technical difficulties and low economic benefits faced by secondary development. Through the research and practice of GGRP (geophysics-geology-reservoir-production) integrated technology, abandoned oil fields are revitalized to ensure high and stable production. In order to cope with the challenges of uncertainty in the distribution of remaining oil, structural complexity, reservoir heterogeneity and temperature limitations of underwater manifolds, we have overcome a series of cutting-edge technical problems. These innovative technologies include remaining oil prediction technology for long-term water flooding shut-in oil fields, geological guidance and fine description technology for complex oil reservoirs, and reservoir pipe flow coupling model flow assurance technology. They have successfully guided the secondary development of oil fields and significantly improved improve the development effect of oil fields. The results show that the initial production capacity of the oil field has jumped to the top three oil fields in the eastern South China Sea. The actual water content rising trend is basically consistent with the plan design, and the increase in recoverable reserves is expected to reach 259×104 m3. This pioneering research provides valuable experience for the secondary development of long-term abandoned deepwater oil fields. This scientific and technological achievement has broad application prospects in the development of similar oil fields.